A cost-based life-cycle pricing model for offshore wind power plants within China's carbon trading scheme. (November 2022) - He, Qianya; Chen, Haoyong; Lin, Zhenjia; Dai, Xinyun; Huang, Yuxiang; Cai, Weijun
Abstract: The development of renewable energy is showing a rapid development trend under the goal of Carbon Emission Peak and Carbon Neutrality. Offshore wind power is significant in the decarbonization of energy and the construction of future power systems. With the support and regulation of the government, offshore wind power is gradually developing on a large scale, and the pricing of renewable energy, including offshore wind power, has become a key research topic in the electricity market. In this paper, a life cycle costing-based pricing model for offshore wind power with carbon trading is constructed. First, the theoretical on-grid electricity price for offshore wind power is calculated, the sensitivity analysis of its influencing factors is then conducted, and the corresponding solutions are proposed at the end. The results show that the price of offshore wind power will gradually decrease, which has the potential to lower the on-grid electricity price and participate in the market competition.